Glucose biosensor based on the hexacyanoferrate 11-mercaptoundecyl-N',N'',N'''-trimethylammonium/6-(Ferrocenyl)hexanethiol - Baldo, Thaisa A. [UNESP]; Seraphim, Patricia M. [UNESP]; Gomes, Homero M. [UNESP]; Teixeira, Marcos F. S. [UNESP] (Elsevier, 2014)
An amperometric glucose biosensor based on on hexacyanoferrate 11-mercaptoundecyl-N',N'',N'''-trimethylammonium (HMA)/ 6-(ferrocenyl)hexanethiol (FT)/GOx modified gold electrode was fabricated and evaluated. The GOx/HMA/FT/Au electrode was characterized using cyclic voltammetry (CV) and used for glucose concentration estimation in standard solutions using CV and amperometric techniques.
Keywords: Amperometric sensor; Biosensor; Glucose oxidase; Self-assembled monolayer